2023
DOI: 10.1007/s12519-023-00714-w
|View full text |Cite
|
Sign up to set email alerts
|

An eighteen-year longitudinal examination of school victimization and weapon use in California secondary schools

Abstract: Background School safety has been a major public health issue in the United States and internationally for more than three decades. Many policies and programs have been developed and implemented to prevent school violence, improve the school climate, and increase safety. There are only a few peer-reviewed studies of changes in school violence over time. The study examined changes over time in school victimization, weapon involvement and school climate, comparing change trajectories by gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The results are relevant, since school climate has been identified as an important variable in reducing school dropout, especially in vulnerable schools [48]. Likewise, international research has shown a relationship between a positive evaluation of school climate and the reduction of violence [49]. Therefore, contributing to improve the school climate is fundamental to favor the academic development of students.…”
Section: Discussionmentioning
confidence: 99%
“…The results are relevant, since school climate has been identified as an important variable in reducing school dropout, especially in vulnerable schools [48]. Likewise, international research has shown a relationship between a positive evaluation of school climate and the reduction of violence [49]. Therefore, contributing to improve the school climate is fundamental to favor the academic development of students.…”
Section: Discussionmentioning
confidence: 99%